Customers' perception towards the programs conducted by Majlis Tindakan Ekonomi dan Sosial Bumiputera Melaka / Mashanim Masrul - Masrul, Mashanim (Faculty of Business and Management, 2007)
Majlis Tindakan Ekonomi dan Sosial Bumiputera (MTESB) as one of the division under Melaka Chief Minister's Department is to focus on the planning, strategy formulation and implementation the efforts to produce and create a Bumiputera Industrial and Commercial Community (Masyarakat Perdagangan dan Perindustrian Bumiputera (MPPB) ) that is competent moving forward and strong in facing challenges. However since, this organization is a public sector, most of the bumiputera's entrepreneur perception and acceptance towards the programs is somehow low. This is because due to not many of the bumiputera's entrepreneur realize the exact function of this organization. The main purpose of this study is somehow to observe the level of customers' perception towards the programs conducted by MTESB and also the factors influence customer perception which are the service provided, quality of the programs and also customer trust. This research is conducted by using non-probability sampling and the sampling method is convenience sampling. The sampling size is 50 respondents, which consist of those who had participated in the programs. From the finding the factor that the most influence customer perception is customer trust. Based on the finding, some recommendations have been suggested in order to help increase customers' perception.